Reducing Stress Levels with Benson Therapy Mothers Who Have Children with Special Needs - Ima Sukmawati; Yuyun Rahayu; Sri Dewi Utami; Al Syifa Rosna Anggraini; Heri Riyanto (Institute of Computer Science (IOCS), 2023)
Mothers of children with special needs may experience higher levels of stress due to stigma, social isolation, care burden, and financial expenses. A complementary therapy that can reduce stress levels is Benson therapy. To determine the effect of Benson therapy on stress levels in mothers of children with special needs. This study used a quantitative analysis method with a quasi-experimental (pre-test and post-test) design. Sampling technique with accidental sampling of as many as 35 respondents. Data collection was done using the DASS questionnaire with 16 question items and observation sheets. The collected data were processed with SPSS version 24.0 and analyzed with the Wilcoxon test. The research was conducted at SLB Negeri Ciamis in August 2023. The study found significant differences in maternal stress levels before and after Benson therapy intervention, from a mean ± SD score of 3.17 ± 0.453 to a mean score of 4.63 ± 0.547. There is an effect of Benson therapy on the stress level of mothers of children with special needs, with a significance level of p-value 0.000 (p < 0.005).